Fujoshi Viewed From Moral Reasoning in Otaku - Rahmawati Rahmawati; Siti Nurhidayah (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2023)
The rise of foreign cultures entering Indonesia has made people, especially teenagers, following popular trend. One of the cultures that infiltrates Indonesia is Japanese culture. Otaku/Weeaboo phenomenon is a common trend among children, teenagers, and adults. One of the negative influences of these trends is having a woman who likes boys' love or yaoi, commonly known as Fujoshi. The present research is qualitative one because it uses interview and observation methods to deeply explore the perceptions of an Otaku based on moral reasoning with interactive data analysis from Miles and Huberman. Using a snowball sampling technique with four subjects and three informants, the results showed that based on moral reasoning on Otaku, three out of four Otaku had a positive perceptions of Fujoshi, while one out of four Otaku had a negative perceptions of Fujoshi.